Landscape code for therapeutic gardens and therapeutic landscapes - Krasilnikova, Elina; Zhuravleva, Inna; Zaika, Inna (project baikal, 2021)
The creation of therapeutic gardens and therapeutic landscapes in the structure of landscaping of hospitals and clinics is an important direction in the formation of the landscape and urban planning framework of cities to avoid the consequences of the pandemic. The landscape code of therapeutic gardens and therapeutic landscapes is scientifically grounded practical guidelines for the architectural and landscape design of the territories of healthcare facilities.